Analysis of Prehospital Documentation of Injury-Related Pain Assessment and Analgesic Administration on the Contemporary Battlefield. (2nd January 2016) - Gerhardt, Robert T.; Reeves, Patrick T.; Kotwal, Russ S.; Mabry, Robert L.; Robinson, John B.; Butler, Frank
Abstract: In addition to life-saving interventions, the assessment of pain and subsequent administration of analgesia are primary benchmarks for quality emergency medical services care which should be documented and analyzed. Analyze US combat casualty data from the Department of Defense Trauma Registry (DoDTR) with a primary focus on prehospital pain assessment, analgesic administration and documentation. Retrospective cohort study of battlefield prehospital and hospital casualty data were abstracted by DoDTR from available records from 1 September 2007 through 30 June 2011. Data included demographics; injury mechanism; prehospital and initial combat hospital pain assessment documented by standard 0-to-10 numeric rating scale; analgesics administered; and survival outcome. Records were available for 8, 913 casualties (median ISS of 5 [IQR 2 to 10]; 98.7% survived). Prehospital analgesic administration was documented for 1, 313 cases (15%). Prehospital pain assessment was recorded for 581 cases (7%; median pain score 6 [IQR 3 to 8]), hospital pain assessment was recorded for 5, 007 cases (56%; median pain score5 [CI95% 3 to 8]), and 409 cases (5%) had both prehospital and hospital pain assessments that could be paired. In this paired group, 49.1% (201/409) had alleviation of pain evidenced by a decrease in pain score (median 4, , IQR 2 to 5); 23.5% (96/409) had worsening of pain evidenced by an increase in pain score (median 3, CI95 2.8 to 3.7, IQR 1 to 5); 27.4% (112/409) had no change; and the overall difference was an average decrease in pain score of 1.1 (median 0, IQR 0 to 3, p < 0.01). Time-series analysis showed modest increases in prehospital and hospital pain assessment documentation and prehospital analgesic documentation. Our study demonstrates that prehospital pain assessment, management, and documentation remain primary targets for performance improvement on the battlefield. Results of paired prehospital to hospital pain scores and time-series analysis demonstrate both feasibility and benefit of prehospital analgesics. Future efforts must also include an expansion of the prehospital battlefield analgesic formulary.